The slip modulus between cold formed steel and timber sheathing based on fastener spacing increment - Liu, Hanwen (Kansas State University, 2018)
The combination of cold formed steel (CFS) with structural wood panels exhibits a degree of partial composite action behavior. In the current design and construction codes, CFS and wood sheathing systems are considered separate, in a non-composite manner, due to the absence of sufficient supporting experimental and research data. The problem with previous research is the lack of information to fully define the composite action between CFS and wood sheathing. The scope of this study is to check fundamental information provided in previous research. The approach adopted to solve the problem follows previous experimental procedures conducted at Kansas State University. The objective of the research is to determine the slip modulus with various fastener spacing. Additional results obtained in this study are compared to previous research results.
Keywords: Cold formed steel-timber sheathing system